Why and how projects in organizations differ? The example of Portuguese profit and non-profit organizations - Eyschen, Kristin (2015)
This research has as a goal to give an overview of what Project Management is in Portugal. The purpose is not to focus on a small picture, but to understand the broad concept and perception of Project Management in Portugal in two very important sectors: Profit- and Non-Profit Sector. Both Profit- and Non-Profit project managers have been interviewed, giving an insight of how different projects are in both sectors and why. This paper will be especially helpful comparing the Project Management maturity of Portugal to other countries regarding these two different point of views.